Future Complexity of Care Tier Affected by Depression Outcomes - Kurt B. Angstman; Matthew R. Meunier; James E. Rohrer; Sara S. Oberhelman; Julie A. Maxson; Parvez A.S. Rahman (SAGE Publishing, 2014)
Background: The inclusion of mental health issues in the evaluation of multimorbidity generally has been as the presence or absence of the condition rather than severity, complexity, or stage. The hypothesis for this study was that clinical outcome of the depression 6 months after enrollment into collaborative care management would have a role in predicting future complexity of care tier. Methods: This study was a retrospective chart review of 1894 primary care patients who were diagnosed with major depressive disorder or dysthymia as of December 2012. Multiple logistic regression analysis was used to test the independent associations between each variable and the odds of being included in the higher tiers (HT) group. Results: Age (odds ratio [OR] = 1.022, confidence interval [CI] = 1.013-1.030, P < .001), female gender (OR = 1.380, CI = 1.020-1.868, P = .037), being married (OR = 0.730, CI = 0.563-0.947, P = .018), and the presence of comorbidities (1, OR = 1.986, CI = 1.485-2.656, P < .001; ≥2, OR = 4.678, CI = 3.242-6.750, P < .001) were independently associated with future HT levels. The presence of persistent depressive symptoms (PHQ-9 ≥10) at 6 months conferred 2.280 (CI = 1.673-3.107, P < .001) times likely odds of HT level compared with clinical remission at 6 months. Conclusion: Patients with the diagnosis of major depression or dysthymia had greater odds of complex tier levels in the future, if depression was not treated to remission by 6 months. This study demonstrated the importance of the goal of significant improvement (ie, remission) of depression symptoms by 6 months (especially those older patients with more comorbidity) from entering into the higher complexity tiers.